Implementation of pharmacist-led services in primary care: A mixed-methods exploration of pharmacists' perceptions of a national educational resource package - Kate Preston; Natalie M. Weir; Tanja Mueller; Rosemary Newham; Marion Bennie (Centro de Investigaciones y Publicaciones Farmaceuticas, 2021)
Background: To help alleviate the global pressure on primary care, there has been an increase in the number of clinical pharmacists within primary care. Educational resources are necessary to support this workforce and their development within this role. An educational resource package was developed in Scotland to support the General Practice Clinical Pharmacists (GPCPs), containing a hard copy Competency and Capability Framework (CCF), an online platform (TURAS) and both clinical and educational supervisors in 2016. Objective: To examine the implementation of a competency-based educational resource package through the exploration of pharmacists' perceptions of its adoption, acceptability, appropriateness, and feasibility. Methods: Participants were GPCPs who had been part of a national training event between 2016 and 2018. The participants were given the opportunity to complete an online questionnaire or a semi-structured telephone interview. Both data collection tools were based on Proctor's model of implementation outcomes: adoption, acceptability, appropriateness and feasibility. Areas covered included GPCPs' perceptions and level of adoption of the educational resource package developed to support them in their role. Results: Of a potential 164 participants, 52 (31.7%) completed the questionnaire and 12 (7.3%) completed the interview. GPCPs indicated widespread adoption and were accepting of the resources; however, it was suggested that its value was undermined, as it was not associated with a qualification. The appropriateness and feasibility of the resources depended on GPCPs' individual situation (including current role, previous job experience, time available, support received from peers and supervisors, and perceptions of resources available). Conclusions: The suitability of the CCF was evidenced by participants' adoption and acceptance of the resource, indicating the necessity of a competence-based framework to support the GPCPs' role. However, its suitability was hindered in terms of varied perceptions of appropriateness and feasibility. Despite the limited sample size, the results indicate that the value of these resources should be promoted across primary care; nevertheless further facilitation is required to allow GPCPs to fully engage with the resources.